PSYCHOLOGICAL PREPARATION OF THE POPULATION FOR EMERGENCY ACTIVITIES (Neo Scientific Peer Reviewed Journal, 2023)
The article discusses the psychological preparation of the population for emergency treatment. The author emphasizes the importance of psychological training for people to deal with emergencies and the role of mental resilience in forming a sense of responsibility to society. The article presents five main tasks of psychological training in emergency situations.